2020
DOI: 10.3390/tropicalmed5020087
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanism of Trypanosoma cruzi Acquisition by Triatomine Insects: Evidence from a Large Field Survey of Triatoma infestans

Abstract: Blood-sucking triatomine bugs transmit the protozoan parasite Trypanosoma cruzi, the etiologic agent of Chagas disease. We measured the prevalence of T. cruzi infection in 58,519 Triatoma infestans captured in residences in and near Arequipa, Peru. Among bugs from infected colonies, T. cruzi prevalence increased with stage from 12% in second instars to 36% in adults. Regression models demonstrated that the probability of parasite acquisition was roughly the same for each developmental stage. Prevalence increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, most program or trial evaluations have relied on house infestation and density indices, and implicitly or explicitly excluded the use of triatomine infection based on its labor-intensive nature and requirement of laboratory equipment and skilled technicians [ 17 – 19 ], with some notable exceptions (e.g. [ 20 , 21 ]). Detection of T. cruzi has usually been conducted by microscopic examination of wet-mount slides containing a drop of rectal contents diluted with saline solution; positive outcomes are based on the presence of either epimastigotes or trypomastigotes.…”
Section: Introductionmentioning
confidence: 99%
“…However, most program or trial evaluations have relied on house infestation and density indices, and implicitly or explicitly excluded the use of triatomine infection based on its labor-intensive nature and requirement of laboratory equipment and skilled technicians [ 17 – 19 ], with some notable exceptions (e.g. [ 20 , 21 ]). Detection of T. cruzi has usually been conducted by microscopic examination of wet-mount slides containing a drop of rectal contents diluted with saline solution; positive outcomes are based on the presence of either epimastigotes or trypomastigotes.…”
Section: Introductionmentioning
confidence: 99%
“…In an entomological survey, Tustin et al [ 12 ] focused on the infection of triatome bugs with T. cruzi. They showed that the prevalence of infection in bugs from residences in Peru increased with stage, and that the prevalence in bugs is associated with the number of bites.…”
mentioning
confidence: 99%